Interspecific Signaling Between the Parasitic Plant and the Host Plants Regulate Xylem Vessel Cell Differentiation in Haustoria of Cuscuta campestris - Kaga, Yuki; Yokoyama, Ryusuke; Sano, Ryosuke; Ohtani, Misato; Demura, Taku; Kuroha, Takeshi; Shinohara, Naoki; Nishitani, Kazuhiko (Frontiers in Plant Science, 2020)
The genus Cuscuta are stem parasitic angiosperms that parasitize a wide range of vascular plants via de novo formation of a distinctive parasitic organ called a haustorium. In the developing haustorium, meristematic cells, which are initiated from the stem cortical tissue, differentiate into haustorial parenchyma cells, which elongate, penetrate into the host tissues and finally connect with the host vasculature. This interspecific vasculature connection allows the parasite to uptake water and nutrients from the host plant. Although histological aspects of haustorial development have been studied extensively, the molecular mechanisms underlying vasculature development and the interspecific connection with the host vasculature remain largely unknown. To gain insights into the interspecific cell-to-cell interactions involved in haustorium development, we established an in vitro haustorium induction system for Cuscuta campestris using Arabidopsis thaliana rosette leaves as the host plant tissue. The in vitro induction system was used to show that interaction with host tissue was required for the differentiation of parasite haustorial cells into xylem vessel cells. To further characterize the molecular events occurring during host-dependent xylem vessel cell differentiation in C. campestris, we performed a transcriptome analysis using samples from the in vitro induction system. The results showed that orthologs of genes involved in development and proliferation of vascular stem cells were up-regulated even in the absence of host tissue, whereas orthologs of genes required for xylem vessel cell differentiation were up-regulated only after some haustorial cells had elongated and contacted the host xylem. Consistent results were obtained by another transcriptome analysis of the haustrorium in C. campestris undergoing parasitization of an intact host plant. These findings suggest the involvement of host-derived signals in the regulation of non-autonomous xylem vessel differentiation and its connection to the host xylem during the haustorium development by activating a set of key genes for differentiation into xylem vessel cells.